PENGARUH BELANJA, PENDAPATAN ASLI DAERAH, DAN TINGKAT PENGANGGURAN TERHADAP INDEKS PEMBANGUNAN MANUSIA PROVINSI JAWA TENGAH - Anggraini, Lina Widya; Desy Nur Pratiwi; M. Hasan Ma’ruf (Jurnal Ilmiah Akuntansi, 2025)
This research aims to determine the effect of government spending, local revenue, and unemployment rate on the human development index of Central Java Province in 2021 – 2023. This research uses quantitative methods with  a total of 105 data, obtained from 35 districts / cities in Central Java Province over a three-year period, namely 2021 to 2023. The data was tested using SPSS 23, using data analysis, namely descriptive statistics, classical assumption tests, and hypothesis testing using multiple linear regression analysis, F test, t test and coefficient of determination test. The results showed that variable government spending and local revenue has significant effect for human development index.  While variable unemployment rate has no significant effect for human development index